Renegosiasi Kontrak Sebagai Upaya Penyelesaian Pelaksanaan Kontrak Saat Pandemi Covid-19 - Syaiful Khoiri Harahap (Fakultas Hukum Universitas Islam Indonesia, 2022)
The COVID-19 pandemic proves the difficulties for business actors to operate their businesses, hence many of them face constraints in fulfilling their obligation to the creditors, which subsequently causes these debtors to be declared in default. Creditors as parties entitled to the fulfillment of the obligation are expected to understand the difficulties faced by debtors due to the COVID-19 pandemic. The problems raised in this study are: first, is the covid-19 pandemic may constitute ground for default by the debtor in fulfilling his contractual obligations, second, how are the efforts to resolve the obstacles in fulfillment of obligation in the covid-19 pandemic. This research was conducted using normative juridical methods and analyzed qualitatively. This study concludes that first, the covid-19 pandemic includes force majeure which resulted in the debtor experiencing economic difficulties to fulfill their obligation, leading to the debtor’s default which consequently resulted in the debtor losing his business and property which was used as collateral for debt repayment; second, if the debtor has difficulty in fulfilling their obligations, the debtor can ask the creditor to carry out renegotiation of the ongoing agreement based on the principle of kinship as mandated by Pancasila and the 1945 Constitution. Key Words: Renegotiation; dispute resolution; default; covid-19 pandemic Abstrak Pandemi covid-19 terbukti telah membuat para pelaku usaha mengalami kesulitan untuk menjalankan usaha, sehingga tidak sedikit pula yang terkendala dalam memenuhi prestasi kepada kreditur sehingga menyebabkan debitur dinyatakan wanprestasi. Kreditur selaku pihak yang menuntut terpenuhinya prestasi harus dapat memahami kesulitan yang dihadapi oleh debitur akibat terjadinya pandemi covid-19. Permasalahan yang diangkat dalam penelitian ini, yaitu: pertama, apakah pandemi covid-19 merupakan wanprestasi oleh debitor dalam pemenuhan prestasi kontraktualnya, kedua, bagaimana upaya penyelesaian kendala pemenuhan prestasi sebagai akibat adanya pandemi covid-19. Penelitian ini dilakukan dengan menggunakan metode penelitian yuridis normatif dan akan dianalisis secara kualitatif. Penelitian ini berkesimpulan bahwa: pertama, pandemi covid-19 termasuk force majeure yang mengakibatkan debitur mengalami kesulitan secara ekonomi untuk memenuhi prestasinya, menyebabkan debitur menjadi wanprestasi yang mengakibatkan debitur kehilangan usaha serta harta bendanya yang dijadikan sebagai jaminan pembayaran utang; kedua, apabila debitur kesulitan memenuhi prestasi, maka debitur dapat meminta kepada kreditur untuk melaksanakan renegosiasi terhadap perjanjian yang sedang berjalan dengan berdasarkan asas kekeluargaan sebagaimana yang diamanatkan oleh Pancasila dan UUD 1945. Kata Kunci: Renegosiasi; penyelesaian sengketa; wanprestasi; pandemi covid-19